GERM-08. EARLIER RECOGNITION OF SYMPTOMS AND DIAGNOSIS MAY REDUCE TREATMENT AND LATE EFFECT BURDEN IN CHILDREN, TEENAGERS AND YOUNG ADULTS WITH INTRACRANIAL GERM CELL TUMOURS. Issue 2 (22nd June 2018) - Hayden, James; Bartels, Ute; Penn, Anthony; Murray, Matthew; Calaminus, Gabriele; Nicholson, James
Abstract: BACKGROUND & AIMS: Prolonged symptom intervals (SI) are frequently seen in malignant intracranial germ cell tumours (iGCTs) and have been associated with inferior outcomes in other brain tumours. This study reviewed the clinical presentation of iGCTs and examined the effect of prolonged SI on this group. METHODS: Clinical data were retrospectively reviewed for patients (diagnosed with an iGCT (January 2002-December 2011) from 6 centres [4 UK (n=45), 1 German (n=11) and 1 Canadian (n=31)]. Fisher's exact test used for comparisons (p<0.05 significant). RESULTS: Study cohort included 87 (58M:29F) patients [59 germinoma, and 28 non-germinoma] with tumours located in pineal (34), suprasellar (25), bifocal (24) and other area (4), of which 16 were metastatic. Median age at diagnosis was 11.5 years (0.6-22.6y). The time to diagnosis from first symptom (SI) ranged from 0-69 months (median 3m, mean 8.5m). A prolonged SI (> 6months) was observed in one third of patients (n=28) and significantly associated with metastatic disease (11/28 vs. 5/59, p=0.002) at diagnosis. In patients with a prolonged SI, endocrine symptoms, particularly diabetes insipidus (DI), were common (75%) but raised intracranial pressure (RICP) was infrequent (14%). In contrast, those with a SI <6 months frequently presented with RICP (84%, p<0.0001). CONCLUSIONS: One third of patients with an iGCT have symptoms >6 months prior to diagnosis. Delayed diagnosis is associated with metastatic disease. Early symptom recognition, particularly related to hormonal disturbances without RICP, may improve timely diagnosis, reduce frequency of metastatic disease and thus reduce the burden of treatment and late-effects.